Naklep in malomarnost ter motivi - Ferlinc, Andrej (Pravnik, 2017)
The relation between motive and intent is according to the author a common will to commit a criminal act. The characteristic of both is an individually planned orientation to reach the target of motive. An intentionally committed criminal offence is only a means to an end when the target of motive is not statuary defined as a criminal offence. On the other side motive is identical with intent when its target causes relevant criminal consequence. With criminal offences committed through negligence, there is no willing purpose towards a selected aim, which would be identical with a criminal result. We are interested what kind of acting can avoid criminal issue. A perpetrator has two contradictory motives: either to prevent prohibited consequences or to avoid any activities.
Keywords: criminal law; kazensko pravo; kazniva dejanja; malomarnost; motiv; naklep